Keupayaan pemasaran dalam kalangan pengusaha kecil makanan halal di Melaka Tengah: satu kajian awal - Sazelin Arif, (Universiti Kebangsaan Malaysia, 2009)
Small enterprises specializing in halal food production are important to the development of Malaysian’s economy and contribute towards reducing unemployment. This paper discusses some findings from a research on the marketing abilities of small entrepreneurs or manufacturers of halal food products. The study was carried out among Bumiputera halal food manufacturers in Melaka Tengah district. Sets of questionnaires were sent out via mail to 55 Bumiputera entrepreneurs around Melaka Tengah district who are registered under Perbadanan Kemajuan Negeri Melaka (PKNM) and listed in Melaka Entrepreneurs Portal. This paper presents the research findings which identified the problems faced by these entreprenuers as well as acknowledging the opportunities that they have by using SWOT analysis. The paper concludes by presenting suggestions on marketing strategies that can be adopted by the government, responsible agencies for SMEs as well as the manufacturers themselves